For a new perspective on the rare diseases field: the motivation of civil associations in debate. - Rogério Lima BARBOSA (Universidade de Brasília, 2015)
Even as a field of few publications, the rare disease begins to awaken the interest of some social groups of scientists seeking to understand the effects that civic associations generate in society. Specifically the subject and more consistently, it is in France that are the first proposals that seek to understand the work done by these associations. Joining some work of researchers in England, Portugal and the US, the prevailing view on the field of rare diseases has a European perspective. In contrast to this view, this work rescues the studies developed for master's thesis to propose a perspective that goes beyond the apparent results of associations and find not only the motivations of militants as also the need for reconfiguration of thought on the field of rare diseases. This need for change is based on the market's identification as the main coordinator of the field of rare diseases. Coordination try to deploy, in Latin America, the same primer imposed in the US and Europe for the sale of medicine under the guise of the sale of healing.